Climbing The Academic Ladder: Lived Experiences of College Students Who are Pantawid Pamilyang Pilipino Program and Tertiary Education Subsidy Grantees - Shekaina R. Orcajada; Jolai Garcia Bolanos; Khyzzia Jezette G. Salazar; Arian C. Mencias; Dena Fe D. Macaya (INKUIRI: Jurnal Pendidikan IPA, 2025)
This research explores the experiences of college students benefiting from the Pantawid Pamilyang Pilipino Program (4P’s) and the Tertiary Education Subsidy (TES) in the Philippines, two government initiatives designed to support impoverished households and disadvantaged students. Through in-depth interviews, the study examines the beneficiaries' experiences, challenges they face, and their coping and budgeting strategies. The research identifies four central themes: the importance of financial security, especially in covering tuition fees; the aspiration to excel in education, fostering optimism and practicality; a prevailing sense of pragmatic optimism in informed spending decisions; and the ability of beneficiaries to effectively prioritize expenditures. These findings have broader implications, potentially guiding policy improvements for the 4P’s and TES programs to enhance their effectiveness. Additionally, they may motivate college students to persevere in their academic pursuits and inspire them to achieve their educational goals.